Timea bioxyasterina sp.n., a new species from the Northeastern coast of Brazil (Demospongiae, Hadromerida) - Mothes, Beatriz; Santos, Cristina P.; de Campos, Maurício A. (Zootaxa, 2004)
A new Brazilian species of Timea is described from 01 51 00 S-43 48 00 W (35.5 m depth). Timea bioxyasterina sp. nov. is set apart from other tropical Western Atlantic species by the possession of tylasters and two categories of oxyasters.